Efektivitas YouTube sebagai Platform Dakwah Kontemporer: Kajian Sentimen Audiens terhadap Ceramah Ustadz Hanan Attaki - Hidayatullah, Sarip; Casram, Casram (Journal of Society and Development, 2024)
In the digital age, technology has penetrated various aspects of life, including religious practices. One important phenomenon is the use of social media by religious communities to carry out, disseminate, and modernize religious practices. This study focuses on analyzing Ustadz Hanan Attaki's lectures on YouTube, particularly in a video titled “Saat Kecewa, Harus Gimana?” (When Disappointed, What Should We Do?). The purpose of this study is to examine how Ustadz Hanan Attaki explains the concept of overcoming disappointment and how the audience responds to the lecture. The research methods used are content analysis and sentiment analysis. Content analysis is conducted to explore the visual and narrative elements in the video, while sentiment analysis is used to categorize audience comments based on positive, negative, or neutral responses. The main data was obtained from Ustadz Hanan Attaki's lecture video and audience comments on YouTube. The results of the study show that Ustadz Hanan Attaki uses an approach that is relevant to the daily lives of the audience, making his message easy to understand and accept. Sentiment analysis shows that the majority of audience comments are positive, indicating that this lecture successfully provides emotional and spiritual support to the audience. This study confirms that social media, especially YouTube, is an effective platform for delivering relevant and useful religious messages to modern society. The findings of this study provide new insights into the dynamics of religion in the digital age and can be used to formulate policies that support the dissemination of religious teachings through digital media. This study also underlines the importance of the role of digital technology in increasing the involvement of the community in understanding religious teachings and overcoming emotional problems such as disappointment.